Pengaruh Konsentrasi Tween 80 terhadap Pembentukan Nanopartikel Polimerik Pullulan–Glabridin - Irmayanti, Irmayanti; Ain Thomas, Nur; Paneo, Mohamad Aprianto; Suyadi, A. Mu’thi Andy; Papeo, Dizky Ramadani Putri (-, 2026)
Nanoparticle-based drug delivery systems have been widely developed to enhance the solubility, stability, and bioavailability of hydrophobic bioactive compounds such as glabridin. Glabridin is a major flavonoid derived from Glycyrrhiza glabra with various pharmacological activities; however, its application is limited due to poor water solubility and susceptibility to degradation. This study aimed to evaluate the effect of Tween 80 concentration on the physicochemical characteristics of pullulan–glabridin polymeric nanoparticles prepared using the nanoprecipitation method. Pullulan was employed as a biodegradable and biocompatible polymer matrix, while Tween 80 was used as a non-ionic surfactant at concentrations of 0.4%, 0.6%, and 0.8%. The nanoparticles were freeze-dried and characterized for particle size, polydispersity index (PDI), zeta potential, entrapment efficiency (EE), drug loading (DL), and Fourier Transform Infrared (FTIR) analysis. The results showed that increasing Tween 80 concentration significantly improved nanoparticle characteristics. Nanoparticles with sizes of 105–145 nm, lower PDI values, and enhanced colloidal stability were obtained. The highest EE (87.60%) and DL (8.76%) were achieved at 0.8% Tween 80. FTIR analysis confirmed the absence of chemical degradation or interaction, indicating stable nanoparticle formation.